The differences of caries prevalence and caries index of children in primary school with UKGS and without UKGS in Kota Batam - Zulkarnain, Ratna Ayu Alia; Riyanti, Eriska; Sasmita, Inne Suherna (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
The purposes of this research were to describe the caries prevalence and caries index of children in primary school with UKGS (SD Kartini I) and without UKGS (SD 009 Bulang) in Kota Batam. Total samples of this research were 193 persons, it is consist of 107 persons from SD Kartini I and 86 persons from SD 009 Bulang. The Chi-Square Test and U Mann-Whitney Test were conducted in this research. The statistical analysis was significant for caries prevalence between children in primary school with UKGS and without UKGS with Ï2table = 2.71 and Ï2calculate = 3.73, whereas def-t index between children in primary school with UKGS and without UKGS was significant with - Ztable = - 1.96 and Zcalculate = - 2.91 with Î± = 0.05. The DMF-T index between children in primary school with UKGS and without UKGS was significant with Ztable = 1.96 and Zcalculate = 6.32 with Î± = 0,05. The conclusions of this study indicate that there were differences of caries prevalence and caries index between children in primary school with UKGS and without UKGS.